The Hydrogeological assessment of watershed Las Abras, province of Chimborazo, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2015)
Morphometric and hydrophysical parameters of Las Abras hydrographic basin, Chimborazo province, were determined by geological mapping and cartographic evaluation. The basin is overlying the Riobamba Formation, which consists of pyroclastic, lahars, lava flows and volcanic conglomerates of Quaternary age. The lithology have medium to high permeability (k= 10-1 – 10-3 cm/s), with primary and fracture porosities. The basin morphometric evaluation indicates an elongated shape because of Rf = 0.22, Cc = 0.17, Kc = 2.40 y Rbu = 5, and a low density drain, Dd = 0.98 Km/Km2, that prevents the creation of violent floods (Sc = 0.98 %). Accordingly, surface water runs slowly with enough time to infiltrate and feed groundwater aquifers, surface water recharge Las Abras local underground aquifer. This feature was tested with geophysics. In conclusion, the basin Las Abras is fit to drive and store groundwater, but not to allow surface runoff flows.
Keywords: Ecuador; Las Abras; morphometric analysis; watershed; electrical tomography